The evidentiary value of respondent's witnesses in civil and criminal cases - Ruhollah Akrami; Azizollah Fahimi (مطالعات فقه و حقوق اسلامی, 2021)
In Imami jurisprudence, the requirement of the rule of "testimony and oath" is that the obligation to present evidence is on the plaintiff and the respondent can provide the ground for issuing a ruling in his favor by swearing. This rule, along with some narrations, has caused the majority of jurists to invalidate the evidence of the respondent.In the present study, jurisprudential sources have been studied in a descriptive and analytical manner, and it has been concluded that the witnesses of the respondent is also valid, and The meaning of the rules and narrations is the validity of such evidence, which has not been taken away from discovery due to the Assumptions of the Wise; Even lawsuits concerning crimes against the body, the primary duty to provide evidence is the responsibility of the accused, and in cases of hadd and ta'zir, the accused's witnesses, according to the Obviation Rule (Darʼ), will cause suspicion of the witnesses of the plaintiff and consequently its invalidity. The law of our country has not explicitly ruled on this issue, but Article 185 of the Islamic Penal Code confirms the selected view of the investigation has been accepted by the legislator.